A bimetallic doped silicon-based material and a method of making the same
Patent Information
- Application Number
- CN202311412692.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种双金属掺杂硅基材料及其制备方法,以解决硅基材料导电性差以及循环过程中的体积膨胀问题
[0039](1)本发明的X金属体相掺杂在Si的能带间隙中引入附加能级降低Si的带隙宽度,从而缩短电子由价带跃迁至导带的距离,提升硅的本征电导率;另一方面X金属与硅合金化形成高强度模量和高电子电导率的SimXn(X为金属材料)合金颗粒,均匀分散在硅基材料基体中,不仅利于释放拉伸应力并防止颗粒开裂和粉化,缓解充放电过程中硅的体积变化,而且还提高电极材料的电子电导率和锂离子扩散系数。表面掺杂Y金属还可形成Li-Y-Si三相界面,保护内层锂化Si相,减少与电解质的副反应,并限制与新暴露的表面反应的大体积变化的影响。
Smart Images

Figure CN117438574B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of negative electrode materials for lithium-ion batteries, specifically relating to a bimetallic doped silicon-based material and its preparation method. Background Technology
[0002] Lithium-ion batteries (LIBs) are currently the most advanced power source for mobile communications, portable electronic devices, electric vehicles (EVs), and energy storage systems. To meet the ever-increasing energy demands, researchers are dedicated to exploring and developing novel anode materials with high energy and power density, long cycle life, and good safety for next-generation lithium-ion batteries. Graphite anode materials, which have been extensively studied, have a theoretical capacity of only 372 mAh·g. -1 This can no longer meet the requirements of new anode materials.
[0003] Silicon-based materials have high specific capacity and volumetric capacity (3579 mAh·g). -1 and 2194mAh·ml -1 Low lithium deintercalation / intercalation discharge sites (average deintercalation potential ≈ 0.4V vs. Li / Li), + With its relatively low voltage hysteresis, high abundance, and low toxicity, silicon has become an effective alternative to graphite anode materials. Micron-sized silicon, in particular, offers advantages over nano-sized silicon, including higher packing density, lower cost, and lower specific surface area, making it even more promising for commercial applications. Currently, the significant volume change (≈300%) of Si during lithium insertion / extraction and the low electronic conductivity of Si are the main bottlenecks hindering the commercialization of micron-sized silicon. Summary of the Invention
[0004] The purpose of this invention is to provide a bimetallic doped silicon-based material and its preparation method to solve the problems of poor conductivity and volume expansion during cycling of silicon-based materials. Based on this, this invention combines a high-temperature calcination method with a high-energy ball milling-calcination method to prepare bimetallic doped silicon-based materials. In this method, the X metal bulk phase doping introduces additional energy levels into the band gap of Si, reducing the band gap width of Si, thereby shortening the distance for electrons to transition from the valence band to the conduction band and improving the intrinsic conductivity of silicon. On the other hand, the X metal alloys with silicon to form Si with high strength modulus and high electronic conductivity. m X n (X is a metallic material) Alloy particles, uniformly dispersed in a silicon-based matrix, not only facilitate the release of tensile stress and prevent particle cracking and pulverization, mitigating the volume change of silicon during charging and discharging, but also improve the electronic conductivity and lithium-ion diffusion coefficient of the electrode material. Surface doping with Y metal can also form a Li-Y-Si three-phase interface, protecting the inner lithiated Si phase, reducing side reactions with the electrolyte, and limiting the impact of large volume changes from reactions with newly exposed surfaces.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0006] A bimetallic doped silicon-based material includes a silicon-based material and a doped metal, wherein the doped metal includes an X metal and a Y metal, wherein the X metal is a bulk dopant uniformly distributed within the silicon-based material, and the X metal is selected from at least one of Mn, Fe, Co, Ti, Ni, and Cu, and the Y metal is a surface dopant distributed on the surface of the silicon-based material, and the Y metal is selected from at least one of Mg, Zn, Al, and Ca.
[0007] By adopting the above technical solution, the X metal is a transition metal without lithium intercalation activity, and its atomic radius and electronegativity are similar to those of silicon, making it easy to dope with silicon. Bulk doping of the X metal introduces additional energy levels into the band gap of Si, reducing the band gap width of Si, thereby shortening the distance for electrons to transition from the valence band to the conduction band and improving the intrinsic conductivity of silicon. On the other hand, alloying the X metal with silicon forms Si with high strength modulus and high electronic conductivity. m X n (X is a metallic material) alloy particles, uniformly dispersed in a silicon-based matrix, not only facilitate the release of tensile stress and prevent particle cracking and pulverization, mitigating the volume change of silicon during charging and discharging, but also improve the electron and lithium-ion diffusion coefficients of the electrode material. Y is a lithium-intercalating metal that can form a Li-Y-Si three-phase interface during cycling, protecting the inner lithium-ionized Si phase, reducing side reactions with the electrolyte, and limiting the impact of large volume changes from reactions with newly exposed surfaces.
[0008] As a further embodiment, the X metal accounts for 2-15% of the total mass of the bimetallic doped silicon-based material. Too low an X doping amount does not significantly improve the intrinsic conductivity of the silicon-based material, while too high an X doping amount leads to capacity loss and easily causes self-agglomeration of the X metal, reducing material uniformity.
[0009] As a further embodiment, the Y metal accounts for 0.2-5% of the total mass of the bimetallic doped silicon-based material. Too low a Y doping level will prevent the formation of a stable alloy interface, while too high a Y doping level will lead to capacity loss in the silicon-based material.
[0010] As a further option, the doping depth of the Y metal is 10-100 nm.
[0011] As a further option, the X metal is selected from Mn, and the Y metal is selected from Mg. Mn has high conductivity, which further improves the conductivity of silicon anodes, while Mg is a light element with high specific capacity and moderate plateau voltage, which can ensure the high capacity of silicon-based materials.
[0012] As a further embodiment, the silicon-based material includes at least one of silicon, silicon oxide, and silicon-carbon composite materials.
[0013] As a further embodiment, the silicon accounts for 80-97.8% of the total mass of the bimetallic doped silicon-based material.
[0014] As a further embodiment, the electronic conductivity of the bimetallic doped silicon-based material is 10. -4 ~10 -2 S / cm, lithium-ion diffusion coefficient is 10 -13 ~10 -12 cm 2 / s.
[0015] A second aspect of the present invention is to provide a method for preparing the bimetallic doped silicon-based material, comprising at least the following steps:
[0016] S1: Under vacuum or inert atmosphere, a mixture of metal powder X and silicon-based material powder is calcined at high temperature to obtain bulk-doped silicon-based material X.
[0017] S2: Under vacuum or inert atmosphere, X bulk doped silicon-based material and Y metal powder are ball-milled and calcined to obtain bimetallic doped silicon-based material.
[0018] By adopting the above technical solution, firstly, after the materials are mixed evenly, they are calcined at high temperature. The high calcination temperature and long time are conducive to deep doping. Then, high-energy ball milling is carried out to achieve surface doping. Finally, calcination further stabilizes the interaction between silicon and metal.
[0019] As a further embodiment, the specific operation of high-temperature calcination of the mixture of X metal powder and silicon-based material powder in S1 is as follows: the X metal powder and silicon-based material powder are ball-milled or ground at low speed to make them evenly mixed, and then placed in a heating device, heated to the target calcination temperature, calcined for a certain time, cooled down, and discharged.
[0020] By adopting the above technical solution, low-speed ball milling or grinding ensures that the X metal powder and silicon-based material powder are mixed evenly, which is beneficial for uniform doping during subsequent high-temperature calcination.
[0021] As a further embodiment, the particle size of the silicon-based material powder is 0.5-20 μm. If the silicon-based material particle size is too small, the specific surface area is high, leading to more side reactions and lower initial efficiency; if the particle size is too large, the expansion is excessive, resulting in poor cycle stability and high cost. Furthermore, excessively large particle sizes are unsuitable for lithium-ion battery materials.
[0022] As a further embodiment, the particle size of the X metal powder is 0.5-10 μm. If the particle size of the X metal powder is too large, the mixing is prone to unevenness, and the metal dispersion is uneven after sintering; if the particle size is too small, the metal powder will agglomerate during the sintering process, affecting the uniformity.
[0023] As a further option, the heating equipment includes any one of a vapor deposition furnace, a tubular furnace, a fluidized bed, and a rotary furnace.
[0024] As a further option, the heating rate is 3-10℃ / min. A low heating rate has no effect on the material properties, but reduces the preparation efficiency; an excessively high heating rate will cause the material to become dense, making lithium intercalation difficult.
[0025] As a further option, the calcination temperature is 1000-1500℃. If the calcination temperature is too low, there is no sintering effect; if the calcination temperature is too high, the metal atoms will agglomerate.
[0026] As a further option, the calcination time is 4-8 hours.
[0027] As a further embodiment, the specific operation of ball milling and calcining the X bulk phase doped silicon-based material and Y metal powder in S2 is as follows: placing the Y metal powder and the X bulk phase doped silicon-based material in a ball mill, ball milling for a certain time, then placing them in a heating device to raise the temperature to the target calcination temperature, calcining for a certain time, cooling down, and discharging the material.
[0028] As a further embodiment, the particle size of the Y metal powder is 0.5-10 μm. If the particle size of the Y metal powder is too large, the distribution during the ball milling process will be uneven, resulting in uneven metal dispersion after sintering; if it is too small, the metal powder will agglomerate during sintering, affecting uniformity.
[0029] As a further embodiment, the high-energy ball milling ball-to-material ratio is 1:1 to 3:1.
[0030] As a further option, the ball milling rate is 300-1000 r / min. If the ball milling speed is too low, the energy generated is low, and the surface doping degree is low; if the speed is too high, the powder and the milling cylinder are in a relatively static state, the ball milling action stops, and the milled material does not generate any impact, which is not conducive to the plastic deformation and alloying process.
[0031] As a further option, the ball milling time is 0.5-2 hours.
[0032] As a further option, the heating equipment includes any one of a vapor deposition furnace, a tubular furnace, a fluidized bed, and a rotary furnace.
[0033] As a further embodiment, the heating rate is 3-10℃ / min.
[0034] As a further embodiment, the calcination temperature is 500-800℃. Short-term sintering within this temperature range after doping can further stabilize the interaction between silicon and the metal.
[0035] As a further option, the calcination time is 1-2 hours.
[0036] A third aspect of the present invention is to provide a negative electrode sheet, comprising a current collector and a negative electrode active material coated on the surface of the current collector, wherein the negative electrode active material comprises the bimetallic doped silicon-based material, or a bimetallic doped silicon-based material prepared by the preparation method described above.
[0037] A fourth aspect of the present invention is to provide a lithium secondary battery, including the aforementioned negative electrode sheet.
[0038] The features and beneficial effects of this invention are as follows:
[0039] (1) The X metal bulk phase doping of the present invention introduces additional energy levels into the band gap of Si, reducing the band gap width of Si, thereby shortening the distance for electrons to transition from the valence band to the conduction band and improving the intrinsic conductivity of silicon; on the other hand, the X metal alloys with silicon to form Si with high strength modulus and high electronic conductivity. m X n (X is a metallic material) Alloy particles, uniformly dispersed in a silicon-based matrix, not only facilitate the release of tensile stress and prevent particle cracking and pulverization, mitigating the volume change of silicon during charging and discharging, but also improve the electronic conductivity and lithium-ion diffusion coefficient of the electrode material. Surface doping with Y metal can also form a Li-Y-Si three-phase interface, protecting the inner lithiated Si phase, reducing side reactions with the electrolyte, and limiting the impact of large volume changes from reactions with newly exposed surfaces.
[0040] (2) The present invention prepares bimetallic doped silicon-based materials by high-temperature calcination combined with high-energy ball milling-calcination. The raw materials used are inexpensive, the equipment used is common and readily available, and the preparation process is simple, which is conducive to mass production. Attached Figure Description
[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0042] Figure 1 This is a mapping diagram of the material obtained in Embodiment 1 of the present invention.
[0043] Figure 2 This is the XRD pattern of the material obtained in Example 1 of the present invention.
[0044] Figure 3 This is the XRD pattern of the material obtained in Example 2 of the present invention.
[0045] Figure 4 This is the XRD pattern of the material obtained in Example 3 of the present invention.
[0046] Figure 5 This is the XRD pattern of the material obtained in Example 4 of the present invention.
[0047] Figure 6 This is the XRD pattern of the material obtained in Example 5 of the present invention.
[0048] Figure 7 The images show the XRD patterns of the Li-Y-Si three-phase formed by the recycling of materials obtained in Examples 1, 6, 7, and 8 of this invention. Detailed Implementation
[0049] This invention provides a bimetallic doped silicon-based material and its preparation method. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the same result. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and fall within the scope of protection of this invention. The method and application of this invention have been described through preferred embodiments. Those skilled in the art can obviously make modifications or appropriate alterations and combinations to the method and application described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0050] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments.
[0051] The sources of some of the raw materials involved in Examples 1-8 and Comparative Examples 1-5 of this invention:
[0052] Mn powder: purchased from Shanghai Naio Nanotechnology Co., Ltd., particle size 1μm;
[0053] Micron-sized silicon powder: purchased from Shanghai Naio Nanotechnology Co., Ltd., with a particle size of 5μm;
[0054] Mg powder: purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., particle size 5μm;
[0055] Fe powder: purchased from Bohuas Nanotechnology Co., Ltd., particle size 5μm;
[0056] Ti powder: purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., with a particle size of 5μm;
[0057] Cu powder: purchased from Bohuas Nanotechnology Co., Ltd., particle size 5μm;
[0058] Ni powder: purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., with a particle size of 5μm;
[0059] Al powder: purchased from Shanghai Naio Nanotechnology Co., Ltd., particle size 5μm;
[0060] Zn powder: purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., particle size 5μm;
[0061] Ca powder: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a particle size of 5μm.
[0062] Example 1
[0063] A method for preparing a MnMg bimetallic doped silicon-based material, the method comprising the following steps:
[0064] (1) Weigh 1g of Mn powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, and evacuate to below 200Pa. Heat at a rate of 5℃·min -1 The temperature was raised to 1100℃ and sintered for 6 hours to obtain Mn bulk doped micron-sized silicon-based material.
[0065] (2) Weigh 9.7g of Mn bulk-doped micron-sized silicon-based material and 0.3g of Mg powder and place them in a high-energy ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2 hours under a nitrogen atmosphere. Then transfer the mill to a tube furnace and heat at a rate of 5℃·min. -1 The temperature was raised to 700℃ and sintered for 2 hours to obtain MnMg bimetallic doped micron-sized silicon-based material.
[0066] The prepared MnMg bimetallic doped micron-sized silicon-based material was found to contain 9.5% Mn and 2.8% Mg by inductively coupled plasma optical emission spectrometry (ICP-OES). XRD patterns at 26°, 41.9°, and 53.7° indicated the presence of the MnSi alloy. However, due to the low Mg doping content, Mg was not detected in the XRD pattern. Figure 1 As shown, the surface doping thickness of Mg is approximately 22 nm. During cycling, Li, Si, and the surface-doped Mg react to form a Li-Mg-Si three-phase structure. After cycling, the grazing-incidence XRD of the material shows characteristic peaks at 20.1°, 23.1°, and 68.9°, indicating the presence of the Li-Mg-Si three-phase interface.
[0067] Example 2
[0068] A method for preparing a FeMg bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0069] (1) Weigh 1g of Fe powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-material ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a ball milling rate of 100r / min for 0.5h to mix them evenly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, evacuate to below 200Pa, heat to 1000℃ at a heating rate of 5℃ / min, and sinter for 6h to obtain Fe bulk doped micron-sized silicon-based material;
[0070] (2) Weigh 9.7g of Fe bulk doped micron silicon-based material and 0.3g of Mg powder into a ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2h under a nitrogen atmosphere. Transfer the ball mill to a tube furnace, turn on the heating to 700℃, and heat at a rate of 5℃ / min for 2h to obtain FeMg bimetallic doped micron silicon-based material.
[0071] The prepared FeMg bimetallic doped micron-sized silicon-based material has an Fe content of 9.6% and a Mg content of 2.7%. The XRD shows characteristic peaks at 17.4°, 45.3°, and 50°, indicating the presence of the FeSi2 alloy. The Mg surface doping thickness is 26 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.1°, 23.1°, and 68.9°, indicating the presence of the Li-Mg-Si three-phase interface.
[0072] Example 3
[0073] A method for preparing a TiMg bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0074] (1) Weigh 1g of Ti powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-material ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a ball milling rate of 100r / min for 0.5h to mix them evenly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, evacuate to below 200Pa, turn on the heating to 1300℃, with a heating rate of 5℃ / min, and sinter for 6h to obtain Ti bulk doped micron-sized silicon-based material;
[0075] (2) Weigh 9.7g of Ti bulk doped micron silicon-based material and 0.3g of Mg powder and place them in a ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2h under a nitrogen atmosphere. Transfer the ball mill to a tube furnace, turn on the heating to 700℃, and heat at a rate of 5℃ / min for 2h to obtain TiMg bimetallic doped micron silicon-based material.
[0076] The prepared TiMg bimetallic doped micron-sized silicon-based material has a Ti content of 9.1% and a Mg content of 2.9%. The XRD shows characteristic peaks at 39°, 42.9°, and 49.5°, indicating the presence of TiSi2 alloy. The Mg surface doping thickness is 31 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.1°, 23.1°, and 68.9°, indicating the presence of Li-Mg-Si three-phase interface.
[0077] Example 4
[0078] A method for preparing a CuMg bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0079] (1) Weigh 1g Cu powder and 9g micron silicon powder, place them in a ball mill jar with a ball-to-material ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a ball milling rate of 100r / min for 0.5h to mix them evenly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, evacuate to below 200Pa, turn on the heating to 1000℃, with a heating rate of 5℃ / min, and sinter for 6h to obtain Cu bulk phase doped micron silicon-based material;
[0080] (2) Weigh 9.7g of Cu bulk doped micron silicon-based material and 0.3g of Mg powder and place them in a ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2h under a nitrogen atmosphere. Transfer the ball mill to a tube furnace, turn on the heating to 700℃, and heat at a rate of 5℃ / min for 2h to obtain CuMg bimetallic doped micron silicon-based material.
[0081] The prepared CuMg bimetallic doped micron-sized silicon-based material has a Cu content of 9.5% and a Mg content of 3.1%. The XRD shows characteristic peaks at 36.8°, 44.9°, and 45.9°, indicating the presence of Cu2Si alloy. The Mg surface doping thickness is 23 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.1°, 23.1°, and 68.9°, indicating the presence of Li-Mg-Si three-phase interface.
[0082] Example 5
[0083] A method for preparing a NiMg bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0084] (1) Weigh 1g of Ni powder and 9g of micron silicon powder, place them in a ball mill jar with a ball-to-material ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a ball milling rate of 100r / min for 0.5h to mix them evenly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, evacuate to below 200Pa, turn on the heating to 1200℃, with a heating rate of 5℃ / min, and sinter for 6h to obtain Ni bulk doped micron silicon-based material;
[0085] (2) Weigh 9.7g of Ni bulk doped micron silicon-based material and 0.3g of Mg powder and place them in a ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2h under a nitrogen atmosphere. Transfer the ball mill to a tube furnace, turn on the heating to 700℃, and heat at a rate of 5℃ / min for 2h to obtain NiMg bimetallic doped micron silicon-based material.
[0086] The prepared NiMg bimetallic doped micron-sized silicon-based material has a Ni content of 9.3% and a Mg content of 2.9%. The XRD shows characteristic peaks at 31°, 35.6°, 45.5° and 76.3°, indicating the presence of NiSi alloy. The Mg surface doping thickness is 17 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.1°, 23.1° and 68.9°, indicating the presence of Li-Mg-Si three-phase interface.
[0087] Example 6
[0088] A method for preparing a MnAl bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0089] (1) Weigh 1g of Mn powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, and evacuate to below 200Pa. Heat at a rate of 5℃·min -1 The temperature was raised to 1100℃ and sintered for 6 hours to obtain Mn bulk doped micron-sized silicon-based material.
[0090] (2) Weigh 9.7g of Mn bulk-doped micron-sized silicon-based material and 0.3g of Al powder and place them in a high-energy ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2 hours under a nitrogen atmosphere. Then transfer the mill to a tube furnace and heat at a rate of 5℃·min. -1 The temperature was raised to 700℃ and sintered for 2 hours to obtain MnAl bimetallic doped micron-based silicon material.
[0091] The prepared MnAl bimetallic doped micron-sized silicon-based material has a Mn content of 9.5% and an Al content of 2.8%. The XRD shows characteristic peaks at 26°, 41.9°, and 53.7°, indicating the presence of the MnSi alloy. The Al surface doping thickness is 37 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.3°, 23.4°, and 69.4°, indicating the presence of the Li-Al-Si three-phase interface.
[0092] Example 7
[0093] A method for preparing a MnZn bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0094] (1) Weigh 1g of Mn powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, and evacuate to below 200Pa. Heat at a rate of 5℃·min -1 The temperature was raised to 1100℃ and sintered for 6 hours to obtain Mn bulk doped micron-sized silicon-based material.
[0095] (2) Weigh 9.7g of Mn bulk-doped micron-sized silicon-based material and 0.3g of Zn powder and place them in a high-energy ball mill jar with a ball-to-material ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2 hours under a nitrogen atmosphere. Then transfer the mill to a tube furnace and heat at a rate of 5℃·min. -1 The temperature was raised to 700℃ and sintered for 2 hours to obtain MnZn bimetallic doped micron-sized silicon-based material.
[0096] The prepared MnZn bimetallic doped micron-sized silicon-based material has a Mn content of 9.2% and a Zn content of 2.6%. The XRD shows characteristic peaks at 26°, 41.9°, and 53.7°, indicating the presence of the MnSi alloy. The Zn surface doping thickness is 19 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.5°, 23.9°, and 69.5°, indicating the presence of the Li-Zn-Si three-phase interface.
[0097] Example 8
[0098] A method for preparing a MnCa bimetallic doped micron-sized silicon-based material, the method comprising the following steps:
[0099] (1) Weigh 1g of Mn powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, and evacuate to below 200Pa. Heat at a rate of 5℃·min -1 The temperature was raised to 1100℃ and sintered for 6 hours to obtain Mn bulk doped micron-sized silicon-based material.
[0100] (2) Weigh 9.7g of Mn bulk-doped micron-sized silicon-based material and 0.3g of Ca powder and place them in a high-energy ball mill jar. Transfer the high-energy ball mill jar to a planetary ball mill with a ball-to-material ratio of 3:1. Ball mill at a rate of 300r / min for 2h under a nitrogen atmosphere. Transfer the mill to a tube furnace and heat at a rate of 5℃·min. -1 The temperature was raised to 700℃ and sintered for 2 hours to obtain MnCa bimetallic doped micron-based silicon material.
[0101] The prepared MnCa bimetallic doped micron-sized silicon-based material has a Mn content of 9.4% and a Mg content of 2.9%. The XRD shows characteristic peaks at 26°, 41.9°, and 53.7°, indicating the presence of the MnSi alloy. The Ca surface doping thickness is 17 nm. After cycling, the grazing incidence XRD of the material shows characteristic peaks at 20.3°, 23.5°, and 70.2°, indicating the presence of the Li-Ca-Si three-phase interface.
[0102] Comparative Example 1
[0103] The negative electrode material used in this comparative example is undoped micron-sized silicon powder.
[0104] Comparative Example 2
[0105] A method for preparing a Mn metal-doped micron-sized silicon anode material, the method comprising the following steps:
[0106] Weigh 1g of Mn powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix them thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, evacuate to below 200Pa, turn on the heating to 1200℃ at a rate of 5℃ / min, and sinter for 6h to obtain Mn bulk-doped micron-sized silicon-based material.
[0107] The prepared Mn metal-doped micron-based silicon material has a Mn content of 9.6%. The XRD shows characteristic peaks at 26°, 41.9° and 53.7°, indicating the presence of MnSi alloy. After cycling, no new characteristic peaks appeared in the grazing incidence XRD of the material, indicating that no Li-Mn-Si three-phase interface was formed.
[0108] Comparative Example 3
[0109] A method for preparing a Mg metal-doped micron-sized silicon-based material, the method comprising the following steps:
[0110] Weigh 9.7g of micron-sized silicon powder and 0.3g of Mg powder and place them in a ball mill jar with a ball-to-powder ratio of 3:1. Transfer the high-energy ball mill jar to a planetary ball mill and ball mill at a rate of 300r / min for 2 hours. Transfer the jar to a tube furnace, turn on the heat to 800℃, and heat at a rate of 5℃ / min for 2 hours to obtain a Mg metal surface doped with micron-sized silicon-based material.
[0111] The prepared Mg metal-doped micron-sized silicon-based material has a Mg content of 2.5% and a Mg surface doping thickness of 23 nm. After cycling, the material's grazing incidence XRD shows characteristic peaks at 20.1°, 23.1°, and 68.9°, indicating the presence of the Li-Mg-Si three-phase interface.
[0112] Comparative Example 4
[0113] A method for preparing VMg bimetallic doped silicon-based material, the method comprising the following steps:
[0114] (1) Weigh 1g of V powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, and evacuate to below 200Pa. Heat at a rate of 5℃·min -1 The temperature was raised to 1100℃ and sintered for 6 hours to obtain V bulk phase doped micron-sized silicon-based material;
[0115] (2) Weigh 9.7g of V bulk doped micron-sized silicon-based material and 0.3g of Mg powder and place them in a high-energy ball mill jar. Transfer the high-energy ball mill jar to a planetary ball mill with a ball-to-material ratio of 3:1. Ball mill at a rate of 300r / min for 2h under a nitrogen atmosphere. Transfer the mill to a tube furnace and heat at a rate of 5℃·min. -1 The temperature was raised to 700℃ and sintered for 2 hours to obtain VMg bimetallic doped micron-based silicon material.
[0116] The prepared VMg bimetallic doped micron-sized silicon-based material has a V content of 9.6% and a Mg content of 2.9%. No VSi alloy characteristic peaks were observed in the XRD, indicating that no VSi alloy was formed during the high-temperature calcination process. Simultaneously, V metal peaks (42°, 61°, and 77°) were observed, indicating inhomogeneous V bulk doping. The Mg surface doping thickness was 23 nm. After cycling, grazing-incidence XRD showed characteristic peaks at 20.1°, 23.1°, and 68.9°, indicating the presence of the Li-Mg-Si three-phase interface.
[0117] Comparative Example 5
[0118] A method for preparing a MnSn bimetallic doped silicon-based material, the method comprising the following steps:
[0119] (1) Weigh 1g of Mn powder and 9g of micron-sized silicon powder, place them in a ball mill jar with a ball-to-powder ratio of 3:1, transfer the ball mill jar to a drum ball mill, and ball mill at a rate of 100r / min for 0.5h to mix thoroughly. Place the mixture in a vacuum evaporation furnace, turn on the vacuum pump, and evacuate to below 200Pa. Heat at a rate of 5℃·min -1 The temperature was raised to 1100℃ and sintered for 6 hours to obtain Mn bulk doped micron-sized silicon-based material.
[0120] (2) Weigh 9.7g of Mn bulk doped micron-sized silicon-based material and 0.3g of Sn powder and place them in a high-energy ball mill jar. Transfer the high-energy ball mill jar to a planetary ball mill with a ball-to-material ratio of 3:1. Ball mill for 2 hours at a ball milling rate of 300r / min under a nitrogen atmosphere. Transfer the mill to a tube furnace and heat at a rate of 5℃·min. -1 The temperature was raised to 700℃ and sintered for 2 hours to obtain MnSn bimetallic doped micron-based silicon material.
[0121] The prepared MnSn bimetallic doped micron-sized silicon-based material has a Mn content of 9.7% and a Sn content of 2.8%. The XRD shows characteristic peaks at 26°, 41.9° and 53.7°, indicating the presence of MnSi alloy. The Sn surface doping thickness is 21 nm. After cycling, no new characteristic peaks appeared in the grazing incidence XRD of the material, indicating that no Li-Sn-Si three-phase interface was formed.
[0122] The bimetallic doped micron-based silicon materials prepared in Examples 1-8 and Comparative Examples 1-5 were used as negative electrode active materials for coin-type lithium-ion batteries. Negative electrodes were prepared and coin half-cells were assembled for testing. The test results are recorded in Table 1.
[0123] The specific fabrication steps are as follows: A negative electrode slurry is prepared by mixing bimetallic doped micron-based silicon material, conductive additive (conductive carbon black), and binder (PAA) in a mass ratio of 8:1:1. The uniformly mixed slurry is coated onto copper foil, vacuum dried at 120°C, rolled, and cut into sheets to obtain the negative electrode. A coin cell is assembled using a lithium metal sheet as the counter electrode to evaluate the electrochemical performance of the material. The electrolyte is 1M LiPF6 dispersed in EC:EMC:DEC = 1:1:1 (Vol%), containing 5 vol% FEC. The separator is a porous polyethylene membrane. The prepared coin cell half-cell is subjected to constant current charge-discharge testing using a charge-discharge apparatus. The discharge cutoff voltage is 0.005V, and the charging cutoff voltage is 1V. The first three charge-discharge cycles are conducted at a current density of 0.1C, and subsequent cycles are conducted at a current density of 0.5C.
[0124] The performance data of the above embodiments and comparative examples are shown in Table 1 below:
[0125] Table 1 Performance data of the embodiments and comparative examples
[0126]
[0127]
[0128] As shown in Table 1, the lithium-ion diffusion coefficient, electronic conductivity, and capacity retention of Example 1 are significantly increased compared to Comparative Example 1. Bulk doping of Mn metal can effectively improve the lithium-ion diffusion coefficient, electronic conductivity, and cycle performance of silicon-based materials. This is attributed to the fact that bulk doping of Mn metal can shorten the distance for electrons to transition from the valence band to the conduction band, thereby improving the intrinsic conductivity of silicon. On the other hand, Mn alloys with silicon to form MnSi with high electronic conductivity. The MnSi alloy is uniformly dispersed in the silicon-based material matrix, which not only helps to release tensile stress and prevent particle cracking and pulverization, but also alleviates the volume change of silicon during charging and discharging. When the Mg doping amount is similar, bulk doping of Mn has the most significant effect on improving the lithium-ion diffusion coefficient, electronic conductivity, and capacity retention. The lithium-ion diffusion coefficient, electronic conductivity, and capacity retention of Example 1 are significantly increased compared to Comparative Example 2, indicating that the silicon-based material with Mg surface doping forms a Li-Mg-Si three-phase interface (see Table 1) during cycling. Figure 7 This protects the inner lithium-ion Si phase, reduces side reactions with the electrolyte, and improves the electrochemical performance of the material.
[0129] The specific embodiments described above are merely preferred embodiments of the present invention. It should be noted that any improvements, substitutions, etc., that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention without departing from the principles and rules of the present invention are included within the protection and disclosure scope of the present invention.
Claims
1. A bimetallic doped silicon-based material, characterized in that, The invention includes silicon-based materials and doped metals, wherein the doped metals include metal X and metal Y. Metal X is a bulk dopant uniformly distributed within the silicon-based material and is selected from at least one of Mn, Fe, Co, Ti, Ni, and Cu. Metal Y is a surface dopant distributed on the surface of the silicon-based material and is selected from at least one of Mg, Zn, Al, and Ca. The X metal accounts for 2-15% of the total mass of the bimetallic doped silicon-based material; The Y metal accounts for 0.2-5% of the total mass of the bimetallic doped silicon-based material; The doping depth of the Y metal is 10-100 nm; The method for preparing the bimetal-doped silicon-based material includes: S1: Under vacuum or inert atmosphere, a mixture of metal powder X and silicon-based material powder is calcined at high temperature to obtain bulk-doped silicon-based material X. S2: Under vacuum or inert atmosphere, X bulk doped silicon-based material and Y metal powder are ball-milled and calcined to obtain bimetallic doped silicon-based material.
2. The bimetallic doped silicon-based material according to claim 1, characterized in that, The X metal is selected from Mn, and the Y metal is selected from Mg.
3. The bimetallic doped silicon-based material according to claim 1, characterized in that, The silicon-based material includes at least one of silicon, silicon oxide, and silicon-carbon composite materials; The silicon-based material accounts for 80-97.8% of the total mass of the bimetallic doped silicon-based material.
4. The bimetallic doped silicon-based material according to claim 1, characterized in that, The electronic conductivity of the bimetallic doped silicon-based material is 10. -4 ~10 -2 S / cm, lithium-ion diffusion coefficient is 10 -13 ~10 -12 cm 2 / s.
5. A method for preparing the bimetallic doped silicon-based material according to any one of claims 1-4, characterized in that, It should include at least the following steps: S1: Under vacuum or inert atmosphere, a mixture of metal powder X and silicon-based material powder is calcined at high temperature to obtain bulk-doped silicon-based material X. S2: Under vacuum or inert atmosphere, X bulk doped silicon-based material and Y metal powder are ball-milled and calcined to obtain bimetallic doped silicon-based material.
6. The preparation method according to claim 5, characterized in that, The specific operation of high-temperature calcination of the mixture of X metal powder and silicon-based material powder in S1 is as follows: the X metal powder and silicon-based material powder are ball-milled or ground at low speed to make them evenly mixed, and then placed in a heating device, heated to the target calcination temperature, calcined for a certain time, cooled down, and discharged. The particle size of the silicon-based material powder is 0.5-20 μm; The particle size of the X metal powder is 0.5-10 μm; The heating equipment includes any one of the following: vapor deposition furnace, tubular furnace, fluidized bed, and rotary furnace; The heating rate is 3-10℃ / min; The calcination temperature is 1000-1500℃; The calcination time is 4-8 hours.
7. The preparation method according to claim 5, characterized in that, The specific operation of high-energy ball milling and calcination of X bulk phase doped silicon-based material and Y metal powder in S2 is as follows: Y metal powder and X bulk phase doped silicon-based material are placed in a ball mill, ball milled for a certain time, then placed in a heating device to be heated to the target calcination temperature, calcined for a certain time, cooled down, and discharged. The particle size of the Y metal powder is 0.5-10 μm; The high-energy ball milling ball-to-material ratio is 1:1-3:1; The ball milling rate is 300-1000 r / min; The ball milling time is 0.5-2 hours; The heating equipment includes any one of the following: vapor deposition furnace, tubular furnace, fluidized bed, and rotary furnace; The heating rate is 3-10℃ / min; The calcination temperature is 500-800℃; The calcination time is 1-2 hours.
8. A negative electrode sheet, characterized in that, It includes a current collector and a negative electrode active material coated on the surface of the current collector, wherein the negative electrode active material includes the bimetallic doped silicon-based material according to any one of claims 1 to 4, or the bimetallic doped silicon-based material prepared by the preparation method according to any one of claims 5 to 7.
9. A lithium secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 8 above.
Citation Information
Patent Citations
Negative electrode active material for battery and preparation method thereof
CN111162269A
Negative electrode material and preparation method thereof, lithium ion battery and terminal
CN112751031A